Defend the State as a Method to Prevent the Threat of Irregular Warfare in Indonesia - Mirza Eka Junaidi; Deni Dadang AR; Lukman Yudho Prakoso (Budapest International Research and Critics University, 2021)
Irregular warfare is the most dangerous scenario that occurs in Indonesia, namely terrorism and radicalism. Terrorist crimes are not only disrupting the stability of the country's security but also concerning the stability of the country's defense. If allowed, the community will be restless and very dangerous for the integrity of the nation and state, if it is not immediately prevented it will certainly be able to divide the nation, one of the government's efforts is through the state defense program. , the problem in research is how can State Defense be used as a Prevention Method against the threat of Irregular Warfare in Indonesia? And how is the implementation of the state defense program in the educational environment? The method used is the analytical descriptive method. In this regard, the state defense program is one of the methods of preventing the threat of irregular warfare in Indonesia, thus the conclusion is that the state defense program is a very effective program to be implemented in Indonesia in the era of the Industrial revolution 4.0, and the threat of irregular warfare shows that prevention is through dissemination. The concepts of state defense in which religiosity values are the main thing.